DWI-MRI: Single, Informative, and Noninvasive Technique for Prostate Cancer Diagnosis - Elhousseiny I. Ibrahiem; Tarek Mohsen; Adel M. Nabeeh; Yasser Osman; Ihab A. Hekal; Mohamed Abou El-Ghar (The Scientific World Journal)
Aim. To evaluate diffusion weighted image-MRI (DWI) as a single diagnostic noninvasive MRI technique for prostate cancer (PCa) diagnosis. Material and Methods. A prospective study was conducted between July 2008 and July 2009. Candidates patients were equal or more than 40 years old, with suspicious digital rectal examination (more than clinical T2) or PSA >4 ng/mL. Informed consent was signed. DWI-MRI was performed at 1.5 T with a body coil combined with a spine coil in consecutive 100 cases. The histopathology of biopsies has been used as reference standard. Two examiners were evaluating MRI and TRUS, both of them were blinded regarding pathological findings. Accuracy, specificity, and sensitivity were statistically analyzed. Results. Based on pathological diagnosis: group A (cancerous); 75 cases and group B (non-cancerous); 25 cases. Mean age was 65.3 and 62.8 years in groups A and B, respectively. Mean PSA was 30.7 and 9.2 ng/mL in groups A and B, respectively. Sensitivity of DWI was 58.3% while specificity was 83.8%. Accuracy of lesion detection was 52.4–77.8% (𝑃<0.05). Moreover, DWI at ADC value 1.2×10−3 mL/sec could determine 82.4% of true positive cases (𝑃<0.05). ADC values were lower with Gleason score ≥7 (𝑃<0.05). Conclusion. DWI could represent a non invasive single diagnostic tool not only in detection and localization but also in prediction of Gleason score whenever DWI is used prior to invasive TRUS biopsy. Furthermore, targeted single biopsy could be planned after DWI to minimize patient morbidity by invasive techniques.